Pelatihan Pengelolaan Keuangan dan Marketing Place UMKM Semanggi di Kampung Semanggi - Susanti, Susanti; Hardini, Han Tantri; Kautsar, Achmad; Kharisma, Fresha (Universitas Negeri Surabaya, 2025)
Semanggi MSMEs have the potential to improve the economy in the Sememi sub-district if the management and existing resources are well utilized by MSME actors. The observed weaknesses of Semanggi MSMEs are the lack of use of digital market place media to market their products and the lack of financial management of MSMEs. The existence of these obstacles has become an inspiration for the PKM team to carry out Community Service (PkM) activities in the form of financial management training and marketing places for Semanggi MSMEs in Semanggi village, Sememi sub-district, Benowo sub-district, Surabaya City so that it is hoped that they will be able to utilize the great potential they already have.The offline PKM activity was carried out on July 8 2024 in Semanggi Village, Sememi Village, Benowo District, Surabaya with a total of 25 participants. The output of this research is the PKM journal, videos of PKM activities uploaded on YouTube, and activities published in several mass media. The benefits for MSME participants are increased knowledge and skills of MSME players so that they are able to increase income generation through good financial management and an increase in digital market place marketing in MSMEs so that indicators for MSMEs moving up a class can be achieved and get appreciation in Surabaya.